An Analysis of Hate Speech Against K-Pop Idols and Their Fans on Instagram and Twitter from The Perspective of Pragmatics - Muhammad Muslim Nasution; Julisah Izar; Istiqomah Husnun Afifah (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2021)
Pragmatics is as a study of meaning conveyed by speakers or researchers and interpreted by listeners or readers. Social media itself is a means of communication that is easily accessed by anyone. Social media itself is a means of communication that is easily accessed by anyone. Everyone is free to reveal anything through their social media accounts. This study aims to describe the forms of hate speech including its illocutionary form found on Instagram and Twitter pages. Hate speech is contradicted to the concept of politeness in a language which is an indicator of linguistic elegance. Instagram and twitter are a social chain that aims to help account owners to share or upload photos to other users. This research used descriptive qualitative. Qualitative methodologies refer to research produces which produce descriptive data: people’s own written or spoken words and behaviours. The data were analysed by using interactive model Technique of Miles, Huberman and Saldana. The object of this study includes comments containing hate speech found on Instagram and Twitter pages. Based on the results of observations on Twitter and Instagram pages, it was found that some of the following data include hate speech aimed at several K-Pop idols and illocutionary comments. The results of the study indicate that 41 comments were indicated as hate speech in the form of insults, 4 comments on defamation, 6 comments on blasphemy, and 2 comments on provocation. Meanwhile, in regards to illocutionary comments, there are 12 assertive utterances, 3 directive utterances, 3 expressive utterances, and 3 declarative utterances.